Improving cost and time control in Malaysian construction industry using building information modelling - Muhammad, Muhammad Tahir (2017)
Cost and time control in construction projects has been one of the most important issues in construction. A successful project should meet not only the quality output standards but also time and budget objectives. The management of cost and control of time are fundamental in every project. An effective cost and time management and control technique for construction projects is important in managing risk of cost overrun and delay in completion of projects. Construction projects are becoming more complex as they involve many stakeholders from different disciplines.